47th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference<BR&amp;gt; 14th AIAA/ASME/AHS Adap 2006
DOI: 10.2514/6.2006-2156
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Approach to Damage Tolerance Design of Aircraft Composite Structures

Abstract: A probabilistic approach to determine design parameters for damage-tolerant composite aircraft structures has been developed. The main criterion for acceptance of a structure is a specified probability of failure. The development of this approach is motivated by the increasing use of damage-sensitive composite aircraft structures. The resulting probabilistic model takes into account a probabilistic assessment of in-service accumulated damage, the ability of non-destructive inspection methods to detect such dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, previous studies 15 on damaged composites have shown that the fatigue life slope remains largely unchanged with damage (Lin and Styuart, 2007).…”
Section: Definition Of a Performance Functionmentioning
confidence: 80%
“…However, previous studies 15 on damaged composites have shown that the fatigue life slope remains largely unchanged with damage (Lin and Styuart, 2007).…”
Section: Definition Of a Performance Functionmentioning
confidence: 80%
“…In this way, millions of different configurations, corresponding to possible fatigue scenarios of the component under investigation, can be simulated to derive the probability of failure as a function of the number of loading cycles. In the field of fatigue design of military aircraft, the USAF has already taken into account the probabilistic methodology 29 and requires a failure probability of less than 10 −7 per flight, although in some cases 30 it has also adopted 10 −8 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, USAF requires for the aircraft structure of long‐term military operations a probability of catastrophic failure at or below 10 −7 per flight. In same cases, even a lower probability of failure per flight is assumed, such as 10. −8 So, it is easily understandable that a high number of computer runs are necessary to evaluate the risk of failure by using the Monte Carlo method.…”
Section: Introductionmentioning
confidence: 99%